NLRP3 Inflammasome in Neurological Diseases, from Functions to Therapies - Song, Limin; Pei, Lei; Yao, Shanglong; Wu, Yan; Shang, You (Frontiers in Cellular Neuroscience, 2017)
Neuroinflammation has been identified as a causative factor of multiple neurological diseases. The nucleotide-binding oligomerization domain-, leucine-rich repeat- and pyrin domain-containing 3 (NLRP3) inflammasome, a subcellular multiprotein complex that is abundantly expressed in the central nervous system (CNS), can sense and be activated by a wide range of exogenous and endogenous stimuli such as microbes, aggregated and misfolded proteins, and adenosine triphosphate, which results in activation of caspase-1. Activated caspase-1 subsequently leads to the processing of interleukin-1β (IL-1β) and interleukin-18 (IL-18) pro-inflammatory cytokines and mediates rapid cell death. IL-1β and IL-18 drive inflammatory responses through diverse downstream signaling pathways, leading to neuronal damage. Thus, the NLRP3 inflammasome is considered a key contributor to the development of neuroinflammation. In this review, we briefly discuss the structure and activation the NLRP3 inflammasome and address the involvement of the NLRP3 inflammasome in several neurological disorders, such as brain infection, acute brain injury, and neurodegenerative diseases. In addition, we review a series of promising therapeutic approaches that target the NLRP3 inflammasome signaling including anti-IL-1 therapy, small molecule NLRP3 inhibitors and other compounds, however, these approaches are still experimental in neurological diseases. At present, it is plausible to generate cell-specific conditional NLRP3 knockout mice via the Cre system to investigate the role of the NLRP3 inflammasome, which may be instrumental in the development of novel pharmacologic investigations for neuroinflammation-associated diseases.